Particulate fraction in amniotic fluid at second trimester. - Jalanko, H (1985)
Amniotic fluid at 15-20 weeks contains high concentrations of microvillar enzymes which serve as markers for the prenatal diagnosis of cystic fibrosis. We found that these enzymes were mostly bound to amniotic fluid particulate fraction which eluted in the void volume on Sepharose 6B chromatography and precipitated in ultracentrifugation at 100,000g. Electron microscopy showed that the particulate fraction comprised membrane fragments and small vesicles. It represented less than 1% of the total protein in cell free amniotic fluid. Sorbitol gradient centrifugation showed heterogeneity in the particulate fraction. The enzyme patterns of amniotic fluid and meconium particulate fractions resembled each other. Antiserum against particulate fraction in amniotic fluid strongly reacted with early meconium and fetal small intestine in immunodiffusion, enzyme immunoassay, and staining with immunoperoxidase. The results suggest that most of the enzyme rich particulate fraction in early amniotic fluid originates in the fetal intestine.